2018 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2018
DOI: 10.1109/icassp.2018.8461622
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analysis and Assessment of the Knee in Osteoarthritis During Walking

Abstract: We examine the relation between the sounds emitted by the knee joint during walking and its condition, with particular focus on osteoarthritis, and investigate their potential for noninvasive detection of knee pathology. We present a comparative analysis of several features and evaluate their discriminant power for the task of normal-abnormal signal classification. We statistically evaluate the feature distributions using the two-sample Kolmogorov-Smirnov test and the Bhattacharyya distance. We propose the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Therefore, these observations highlight the importance of the spectrum features that fall within the two identified bands of frequencies and show that these features have a strong impact on the classification performance. In the analysis of our previous work, [35], it was observed that the top performing features obtained from the magnitude spectrum are primarily at the low frequencies. This is further supported here where we have also identified specific bands that carry significantly discriminant information.…”
Section: B Data Acquisition and Test Protocolmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, these observations highlight the importance of the spectrum features that fall within the two identified bands of frequencies and show that these features have a strong impact on the classification performance. In the analysis of our previous work, [35], it was observed that the top performing features obtained from the magnitude spectrum are primarily at the low frequencies. This is further supported here where we have also identified specific bands that carry significantly discriminant information.…”
Section: B Data Acquisition and Test Protocolmentioning
confidence: 95%
“…Table II reports the frame length value that gave the highest AUC per feature set, found using SVM l . A corresponding score, S c , computed as S c = MCC + (1 − E r ) + F 0.5 /3, [35], is also used and consists of the MCC and F 0.5 measures which capture different attributes of the classification result than the AUC and would therefore be useful in the analysis. S c can vary between 0 and 1 (where S c = 1 indicates perfect prediction).…”
Section: Local Search In the Vicinity Of The Best Frame Lengthmentioning
confidence: 99%
See 1 more Smart Citation